Analisis Faktor-faktor Yang Mempengaruhi Kinerja Melalui Etos Kerja Islami Pada Karyawan Rumah Sakit Khusus Ginjal Rasyida Medan - Mustapa Kamal Rokan; Rizal Agus; Elda Rosni Dalimunthe (ITB AAS INDONESIA Surakarta, 2022)
This paper aims to examine the effect of the work environment, religiosity, leadership and training on employee performance through an Islamic work ethic for employees of the Rasyida Special Kidney Hospital Medan. Data were obtained from medical and medical support employees who are Muslim who have been actively working for the past year at the Rasyida Special Kidney Hospital, Medan. By providing a statement questionnaire to 104 respondents. The analytical method used is Path Analysis. The results showed that the variables of the work environment and leadership had no effect on the Islamic work ethic, while the variables of religiosity and training had an effect on the Islamic work ethic. work environment and training variables have no effect on the performance variable. While the variables of religiosity, leadership and Islamic work ethic have a positive and significant effect on the performance variable. And the Islamic work ethic variable cannot mediate the four independent variables on the dependent variable, namely the performance variable.